Welding of pipelines and related facilities - American Petroleum Institute (API) (API)
This standard covers the gas and arc welding of butt, fillet, and socket welds in carbon and low-alloy steel piping used in the compression, pumping, and transnission of crude petroleum. petroleum products, fuel gases, carbon dioxide, nitrogen, and where applicable, covers welding on distribution systems